The science and practice of micronutrient in clinical nutrition : the importance of micronutrient evaluation - Siska Darmayanti (Indonesian Nutrition Association, 2023)
Micronutrients play a crucial role in maintaining good health as they are required for various processes within the body. Every individual has different micronutrient needs depending on their metabolic condition. To achieve optimal health, these needs must be met adequately.